Le penchant politique de Basile Lakapènos pour l’Athos et le rétablissement des relations de Basile II avec le monastère de Stoudios en 985/986 - ΒΛΥΣΙΔΟΥ Βασιλική (Byzantina Symmeikta, 2016)
The Political Inclination of Basil Lakapenos towards Athos and the Reconnection of Basil II with the Monastery of Stoudios in 985/986 This study attempts to show that the only time that Basil II was unable to express his commitment to the Monastery of Stoudios was the period of omnipotence of Basil Lakapenos who, having broken with Antony III and the Stoudites, made clear his own preference for the monastic community of Mount Athos. After the expulsion of the domineering Lakapenos, Basil II resumed his habitual annual visits to the Monastery of Studios, which his ancestors had honored. His reconnection with the monastery in 985/986 seemed to be the only action with which the emperor could express his detachment from the options of Basil Lakapenos in ecclesiastical matters. Basil II had a long road ahead to definitively resolve issues having to do with his relationship to the senior clergy.